Poly(lactic acid) and poly(lactic-co-glycolic acid) particles as versatile carrier platforms for vaccine delivery. (December 2014) - Pavot, Vincent; Berthet, Morgane; Rességuier, Julien; Legaz, Sophie; Handké, Nadège; Gilbert, Sarah C; Paul, Stéphane; Verrier, Bernard
The development of safe and effective vaccines for cancer and infectious diseases remains a major goal in public health. Over the last two decades, controlled release of vaccine antigens and immunostimulant molecules has been achieved using nanometer or micron-sized delivery vehicles synthesized using biodegradable polymers. In addition to achieving a depot effect, enhanced vaccine efficacy using such delivery vehicles has been attributed to efficient targeting of antigen presenting cells such as dendritic cells. Biodegradable and biocompatible poly(lactic acid) and poly(lactic- co -glycolic acid) polymers belong to one such family of polymers that have been a popular choice of material used in the design of these delivery vehicles. This review summarizes research findings from ourselves and others highlighting the promise of poly(lactic acid)- and poly(lactic- co -glycolic acid)-based vaccine carriers in enhancing immune responses.